Low-cycle fatigue crack growth in brittle materials: Adaptive phase-field modeling with variable-node elements - Zhang, Tiancheng; Hirshikesh; Yu, Tiantang; Ding, Junlei; Natarajan, Sundararajan (Computer methods in applied mechanics and engineering, 2024)
This work presents an adaptive phase field framework for the simulation of crack nucleation and propagation in brittle materials subject to low-cycle loading. We introduce a fatigue history strain parameter within the phase-field framework to capture the fatigue effect. The resulting coupled differential equations are solved using a staggered iteration scheme. In order to improve the computational efficiency of the phase-field model, an adaptive refinement scheme is introduced. This scheme utilizes an artificial threshold that takes into consideration of both phase-field variables and cumulative fatigue history field variables to determine the elements to be refined. The handling of the hanging nodes resulting from mesh refinement is accomplished through the application of the variable-node element technique, offering a flexible and efficient mesh integration technique. We validate our proposed numerical scheme through five representative numerical examples: single-edge cracked specimen, compact tension specimen, double-edge cracked panel, plate with a hole and plate with multi-cracks and hole. The results demonstrate that the adaptive mesh refinement scheme significantly reduces computational costs without compromising the accuracy of the numerical predictions. •Fracture due to low cyclic loading is simulated by an adaptive phase-field method.•Variable-node elements for handling the mismatching meshes are adopted.•An artificial threshold is employed to perform adaptive local refinement.•Adaptive mesh refinement scheme retains accuracy at a low cost.•Simulated results demonstrate the robustness of the proposed method.